Measuring Time Use in Surveys: How Valid Are Time Use Questions in Surveys? Concordance of Survey and Experience Sampling Measures - Bettina Sonnenberg; Michaela Riediger; Cornelia Wrzus; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Since it is still unclear to what extent time allocation retrospectively reported in questionnaires, reflects people's actual behavior, examining the accuracy of responses to time use survey questions is of crucial importance. We analyze the congruence of time use information assessed through retrospective questionnaires and through experience sampling methodology. The sample comprised 433 individuals ranging in age from 14 to 86 years. Participants completed standard survey questions on time allocation. In addition, a mobile-phone based experience sampling technology was used over a period of three weeks to obtain snapshots of, on average, 54 momentary activities in which participants participated while pursuing their normal daily routines. Experience sampling assessments were scheduled six times a day over at least nine days, including workdays, Saturdays, andSundays. Results indicate that the congruence between time allocation assessed with survey questions (i.e. in SOEP) and time allocation assessed with experience sampling methodology depends on the characteristics of the respective activities. Associations between standard survey questions and experience sampling methods are quite substantial for long-lasting and externally structured activities, such as paid work on workdays. Incontrast, associations between survey and experience sampling methods are somewhat weaker, though highly statistically significant, for less externally structured, short-term and infrequent activities, such as errands, housework, and leisure. These moderate and relatively small correlations may indicate either an error-prone estimation of the prevalence of shortterm and infrequent activities by experience sampling or respondents' overrating of sporadic and short activities in survey questions. We conclude that activities with a long duration, such as paid work, can be measured in a satisfactory manner using short survey questions. Futureresearch is necessary to elucidate which method (experience sampling method or survey questions) delivers more reliable and valid measures for shortterm and sporadic activities.Day Reconstruction Methods (DRM) should be included in this future methodological research.
Keywords: C21; C83; C93; D10; 330; Survey methods; experience sampling method; validity; time use; market work; housework; leisure; German Socio-Economic Panel Study; MMAA; SOEP; Zeitverwendung; Messung; Panel; Stichprobenerhebung; Deutschland